Beaton’s guidelines in cross-cultural adaptation studies in Brazil: a systematic review - Maiara Medeiros dos Santos Bento; Carina Sousa Elias; Patrícia Carla de Souza Della Barba (O Mundo da Saúde)
This study aimed to evaluate the application of the guidelines proposed by Beaton et al. in Brazil for the cross-cultural adaptation of health instruments into Brazilian Portuguese. A systematic review was conducted of articles published between 2015 and 2022 in the BVS, CINAHL, MEDLINE, and SCOPUS databases. Open-access articles that detailed the cross-cultural adaptation process based on the steps proposed by Beaton et al. were included. Review articles, studies published before 2015, or those that did not detail the adaptation steps were excluded. Analysis of the 27 selected articles revealed that only 7 fully followed Beaton et al.’s guidelines. Changes to the steps were common: pre-testing (11 studies), synthesis (7), translation (6), expert committee (5), and back-translation (2). Furthermore, 11 articles combined other methodologies, 10 added steps, 5 excluded steps, and 6 altered the proposed order. It was concluded that the work of Beaton et al. remains a key reference in the literature, and the proposed steps have proven feasible and applicable in Brazilian cross-cultural adaptation studies. However, frequent modifications suggest the need to further study the Brazilian context to understand the possibilities for developing country-specific practical guidelines.